2022
DOI: 10.3233/mnm-211537
|View full text |Cite
|
Sign up to set email alerts
|

Influence of physical activity, the Mediterranean diet and sociodemographic variables on the values of different cardiovascular risk scales

Abstract: INTRODUCTION: Cardiovascular disease (CVD) continues to be one of the main causes of morbidity and mortality in the world. There are several risk factors for CVD, many of which are preventable, including sedentary lifestyles and poor diet. OBJECTIVE: To assess the influence of physical activity, adherence to the Mediterranean diet and sociodemographic variables such as age, sex and social class on the values of different cardiovascular risk scales. METHODS: A descriptive, cross-sectional study in 1584 Spanish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Additionally, the SUN project described that sedentary attitudes related to computer use were associated with more depressive states in the population [67]. It is obvious that health policies must try to integrate the practice of physical activity in the Spanish population, to reduce the cardiovascular risk that is increased by following a sedentary lifestyle and potential mental illness [68].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the SUN project described that sedentary attitudes related to computer use were associated with more depressive states in the population [67]. It is obvious that health policies must try to integrate the practice of physical activity in the Spanish population, to reduce the cardiovascular risk that is increased by following a sedentary lifestyle and potential mental illness [68].…”
Section: Discussionmentioning
confidence: 99%
“…Physical activity has been positively associated with the reduction of musculoskeletal [ 34 ] and major non-communicable diseases [ 35 , 36 ]; furthermore, mental conditions [ 37 ] can benefit from its regular and tailored practice. Previous studies reported substantial benefits of physical activity on psychological conditions, such as burnout [ 38 , 39 ], anxiety [ 40 , 41 ], or depression [ 42 ].…”
Section: Discussionmentioning
confidence: 99%